Islamic Financial Markets and Institutions. - Hassan, Abul; AlMaghaireh, Aktham Issa; Islam, Muhammad Shahidul (London , Routledge, 2023)
This timely and unique book focuses on the foundations of Islamic financial markets and institutions, in the context of various products, their market application, Islamic asset management and regulation.
Include bibliography reference and index material.
Keywords: Finance; Islamic Banking; Business and Economics